H-Man : refinement of a planar, 2dof robotic manipulandum for use in clinical settings and at home - Ang, Liang Jie (2019)
The H-Man is a robotic rehabilitation device that was made primarily for the use in therapy of the motor function of the arm. The H-Man currently lacks on-screen feedback for the use of trunk compensational strategies and this project looks at the integration of an inertial measurement unit (IMU), which can be used to detect the orientation of the trunk. This improvement is aimed at better aiding the rehabilitative efforts of stroke patients who have suffered arm motor function deficits during the incident as well as the therapists who seek to quicken their recovery. The consequence of allowing compensational strategies to go on in therapy could lead do a hindrance in full motor function recovery. This, coupled with the idea of errorless learning, has also motivated this project to recommend three changes to the current H-Man set up namely in implementing a visual feedback system, as well as reviewing and changing the forces the H-Man generates to facilitate this rehabilitation.